2017
DOI: 10.3390/e19040137
|View full text |Cite
|
Sign up to set email alerts
|

Impact Location and Quantification on an Aluminum Sandwich Panel Using Principal Component Analysis and Linear Approximation with Maximum Entropy

Abstract: Abstract:To avoid structural failures it is of critical importance to detect, locate and quantify impact damage as soon as it occurs. This can be achieved by impact identification methodologies, which continuously monitor the structure, detecting, locating, and quantifying impacts as they occur. This article presents an improved impact identification algorithm that uses principal component analysis (PCA) to extract features from the monitored signals and an algorithm based on linear approximation with maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In view of the optimization problem posed in Equation (24) for supervised learning, maximizing the entropy requires a weight solution that commits the least to all of the database samples [53].…”
Section: Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the optimization problem posed in Equation (24) for supervised learning, maximizing the entropy requires a weight solution that commits the least to all of the database samples [53].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The principal advantage is that new data can be easily incorporated into the training database with no need to re-train the algorithm as in the case of ANNs. The LME algorithm was first developed for damage assessment [21,22], and Sanchez et al [23] and Meruane et al [24] employed it in impact identification.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emission has the characteristics of real-time, online, mature technology, low resource occupancy, relatively simple system and strong environmental adaptability, which is a very effective impact sensing and localization method. In this regard, some scholars have also conducted related research [36][37][38][39][40]. Through the maximum entropy linear approximation method, the four sensors were used to sense and locate the hammer impact on the aluminum plate, and compared with the artificial neural network and the support vector machine, it is found that it has better locating results and requires fewer parameters to be determined [37].…”
Section: Introductionmentioning
confidence: 99%
“…Through the maximum entropy linear approximation method, the four sensors were used to sense and locate the hammer impact on the aluminum plate, and compared with the artificial neural network and the support vector machine, it is found that it has better locating results and requires fewer parameters to be determined [37]. An impact recognition algorithm-based on principal component analysis and maximum entropy linear approximation was proposed to locate and quantify impact in aluminum and aluminum sandwich panels [39].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of debonding detection, the linear dynamic FEA has been carried out in [49] to highlight the relative changes of dynamic response between a healthy sandwich plate and a debonded one. More advanced techniques using modal dataset to detect debonding in sandwich structures can be found in some recent works, for example, [50][51][52].…”
Section: Introductionmentioning
confidence: 99%